Nematode control failure due to anthelmintic resistance in a sheep farm in Malaysia: First identification of the f200y mutation in the isotype 1 β-tubulin gene - Khadijah, S.; Wahaf, A.N.S.; Syahmi, M.I.; Tan, Tiong Kai; Low, Van Lun; Azrul, Lokman Mohd; Chong, Ju Lian; Lim, Yvonne Ai Lian; Abdullah, C.I. (Malaysian Society of Parasitology and Tropical Medicine, 2018)
This paper reports total nematode anthelmintic resistance towards albendazole, fenbendazole, levamisole and ivermectin in a commercial sheep farm located in Terengganu, Malaysia. Faecal Egg Count Reduction Test (FECRT) was conducted on 25 sheep, where five sheep in each group were treated with the respective four anthelmintics based on live bodyweight. The balance of five sheep placed in the control group were not treated with any anthelmintics. At day 13 post-treatment, faecal egg count was conducted and nematode worm egg count reduction percentage was calculated to determine the resistance status towards the respective anthelmintics tested. Results showed that nematodes were resistant to all the anthelmintics tested, namely albendazole, fenbendazole, levamisole and ivermectin with reduction percentage of 87%, 46%, 94% and 68%, respectively. Subsequently, the third stage larvae of Haemonchus contortus and Trichostrongylus colubriformis recovered from post-treatment faecal cultures were subjected to allele-specific polymerase chain reaction (AS-PCR) assay to determine the presence of the benzimidazole resistance gene. This study reports the occurrence of the classical F200Y mutation in the isotype 1 β-tubulin gene, for the first time in Malaysia.